Helping Your Child with Homework - Heidi Liss Radunovich (EDIS, 2006)
FCS2255, a 3-page fact sheet by Heidi Liss Radunovich, will aid parents as they help children complete their homework. Includes a list of ten concrete suggestions to make homework time painless and successful. Also gives background on how much homework to expect at different ages and on when to ask for outside help. Published by the UF Department of Family, Youth and Community Sciences, October 2006.